Amino acid profile and safety assessment of infant formula available in local market, Pakistan. Issue 1 (1st January 2021) - Saeed, Farhan; Ullah Khan, Azmat; Mushtaq, Zarina; Afzaal, Muhammad; Niaz, Bushra; Hussain, Muzzamal; Hameed, Ayesha; Ahmad, Awais; Anjum, Faqir M; Suleria, Hafiz Ansar
ABSTRACT: The objective of the present research work was to explore the nutritional composition of different infant formulas and determine the safety status of these products. For this purpose, different infant formula brands were procured from the local market of Faisalabad, Pakistan. After the collection of these different brands, nutritional composition, i.e. fat, protein, ash, moisture and fiber was determined whilst the microbial analysis, such as Salmonella, Yeasts and Molds Count, and Total Bacteria Count, was carried out through their methods. In addition, the amino acid profile was assessed through paper chromatography. Furthermore, an appropriate statistical design was carried out to determine the level of significance. Mean values for amino acids, i.e. lysine, valine and cysteine varied from 3.06 g/100 g to 6.63 g/100 g, 4.90 g/100 g to 6.51 g/100 g, and 2.32 g/100 g to 3.04 g/100 g, respectively, in different brands of infant formula. Moreover, moisture content, crude proteins, crude fat, crude fiber, ash content, and nitrogen-free extract (NFE) varied from 1.6% to 3.83%, 10.55% to 14.67%, 9.82% to 26.63%, 1.00% to 4.13%, 1.87% to 4.20%, and 51.03% to 69.17%, respectively. It is evident from the microbiological analyses that Salmonella was not present in any brand of infant formula. Whereas yeast and mold counts were ≤2 cfu/g to ≤10 cfu/g in different brands. Moreover, total bacteria count was exhibited in the range of 1.5 × 10 3 cfu/g to 6.3 × 10 3 cfu/g among different brands. Local infant formulas contained high amounts of heavy metals, i.e. 0.99 pp, of lead content followed by cadmium and aluminum as 0.28–0.98 ppm and 1.48–2.05 ppm, respectively. Conclusively, it is evident from whole research that local brands contained higher contents of heavy metal as compared to branded.